Strategic Investment Funds : Opportunities and Challenges - Halland, Havard; Noel, Michel; Tordo, Silvana; Kloper-Owens, Jacob J. (World Bank, Washington, DC, 2016)
Over the past 15 years, the number of government-sponsored strategic investment funds has grown rapidly in countries at all income levels. This paper identifies some of the challenges that these funds face in their endeavor to achieve economic policy objectives while also securing commercial financial returns—the so-called double bottom line. Through the review of the objectives, investment strategies, and operations of a sample of strategic investment funds, this paper outlines ways in which these challenges have been addressed. The paper suggests that properly structured and managed strategic investment funds can be effective vehicles for crowding in private investors to priority investments, thus magnifying the impact of public capital. However, their success rests on the funds' ability to balance policy and commercial objectives, source investment opportunities, and secure the right fund management capacity.